Prokem Language in Facebook Social Media: A Sosiolinguistic Review - Resnita Dewi (Universitas Cokroaminoto Palopo, 2022)
The study aims to analyze the forms of prokem language in Facebook social media and their effect on the position of Indonesian. This research is a type of qualitative descriptive research. Data in the form of prokem language in Facebook social media. Data is collected with (1) observation techniques, (2) documentation, and 3) recording techniques. The results showed that the prokem language in Facebook social media has 4 forms, namely (1) basic word form, (2) abbreviation form, (3) acronym form, (4) phrase form. Prokem language has both negative and positive influences on Indonesian.